Cardiomyocyte‐Specific Snrk Prevents Inflammation in the Heart. Issue 22 (19th November 2019) - Thirugnanam, Karthikeyan; Cossette, Stephanie M.; Lu, Qiulun; Chowdhury, Shreya R.; Harmann, Leanne M.; Gupta, Ankan; Spearman, Andrew D.; Sonin, Dmitry L.; Bordas, Michelle; Kumar, Suresh N.; Pan, Amy Y.; Simpson, Pippa M.; et al.
Abstract : Background: The SNRK (sucrose‐nonfermenting–related kinase) enzyme is critical for cardiac function. However, the underlying cause for heart failure observed in Snrk cardiac conditional knockout mouse is unknown. Methods and Results: Previously, 6‐month adult mice knocked out for Snrk in cardiomyocytes (CMs) displayed left ventricular dysfunction. Here, 4‐month adult mice, on angiotensin II (Ang II) infusion, show rapid decline in cardiac systolic function, which leads to heart failure and death in 2 weeks. These mice showed increased expression of nuclear factor κ light chain enhancer of activated B cells (NF‐κB), inflammatory signaling proteins, proinflammatory proteins in the heart, and fibrosis. Interestingly, under Ang II infusion, mice knocked out for Snrk in endothelial cells did not show significant systolic or diastolic dysfunction. Although an NF‐κB inflammation signaling pathway was increased in Snrk knockout endothelial cells, this did not lead to fibrosis or mortality. In hearts of adult mice knocked out for Snrk in CMs, we also observed NF‐κB pathway activation in CMs, and an increased presence of Mac2 + macrophages was observed in basal and Ang II–infused states. In vitro analysis of Snrk knockdown HL‐1 CMs revealed similar upregulation of the NF‐κB signaling proteins and proinflammatory proteins that was exacerbated on Ang II treatment. The Ang II–induced NF‐κB pathway–mediated proinflammatory effects were mediated in part through protein kinase B or AKT, wherein AKT inhibition restored the proinflammatory signaling protein levels to baseline in Snrk knockdown HL‐1 CMs. Conclusions: During heart failure, SNRK acts as a cardiomyocyte‐specific repressor of cardiac inflammation and fibrosis.